Improving the competence of Geography teachers through training in Mobile-RPG development based on serious games - Putra, Alfyananda Kurnia; Septiana, Wahyu Dwi; Khalidy, Diky Al; Sahrina, Alfi; Arinta, Dicky; Wahyuningtyas, Neni; Habibah, Khoirul; Kholifah, Evalia Nurul (IAIN Madura, 2025)
Based on the analysis of the situation, problems, and needs of MGMP Geography in Malang City, teachers experience obstacles in developing and using technology-based, innovative learning media, namely mobile role-playing games based on serious games. The purpose of community service activities is to provide training in the development of mobile role-playing game learning media based on serious games, which are games designed for specific educational goals, rather than just entertainment, and are formatted as mobile role-playing games (RPGs). This activity also aims to measure the resulting improvement in the teachers' competence. This community service activity employed a participatory training approach, structured into four phases: assessment, preparation, implementation, and evaluation, utilizing a combination of online and offline methods. The subjects in this activity were 50 teachers from MGMP Geography, Malang City. The Wilcoxon test revealed that implementing service activities had a positive impact on improving teachers' competence. In addition, the suggestion from this activity is that similar activities are needed as a form of sustainability for real efforts to improve teacher competence and the quality of geography learning.[Berdasarkan analisis situasi, permasalahan, dan kebutuhan terhadap MGMP Geografi Kota Malang, guru mengalami kendala dalam mengembangkan dan memanfaatkan media pembelajaran inovatif berbasis teknologi. yaitu mobile role-playing game berbasis serious game, yaitu permainan yang di desain untuk pendidikan, bukan hanya untuk bersenang-senang, dalam format role-playing game (RPG). Tujuan kegiatan pengabdian kepada masyarakat yaitu memberikan pelatihan pengembangan media pembelajaran mobile role-playing game berbasis serious game dan mengukur tingkat kompetensi guru. Kegiatan pengabdian ini menggunakan pendekatan pelatihan partisipatif yang terdiri dari empat tahapan, yaitu asesmen, persiapan, pelaksanaan, dan evaluasi, dengan kombinasi daring dan luring. Subjek dalam kegiatan ini adalah MGMP Geografi Kota Malang sebanyak 50 guru. Berdasarkan uji Wilcoxson menunjukkan implementasi kegiatan pengabdian berdampak positif terhadap peningkatan kompetensi guru. Selain itu, saran dari kegiatan ini yaitu diperlukan kegiatan serupa sebagai bentuk keberlanjutan terhadap usaha nyata dalam meningkatkan kompetensi guru dan kualitas pembelajaran Geografi.]